Military logistics research advances and future trends - Daras, Nicholas J.; Kaimakamis, George; Zeimpekis, Vasileios (Operations research/computer science interfaces series ;, 2015)
The book aims to bridge the gap between the abundant literature on commercial logistics and its scarce defense and combat counterpart. Ultimately this book should provide a relevant platform for the latest contributions of operations management, operations research, and computational intelligence towards the enhancement of military logistics.